OPPORTUNITIES AND CHALLENGES FOR TOURISM DEVELOPMENT IN THE NUSA TENGGARA TIMUR REGION (NTT) - Sudini, Luh Putu (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2019)
Besides the tourism sector can increase economic growth, it also does not damage the environment and even stimulates environmental conservation. The tourism sector has become a global trend in the past three decades. World Travel and Tourism Council (WTTC) in 1998. Problems: 1) What is the urgency of tourism in the NTT region? And 2) How do you deal with the challenges of developing tourism in the NTT region? This research is empirical legal research. The urgency of tourism in the NTT region, among others: paying attention to tourism in the province of East Nusa Tenggara (NTT), which has the character of an archipelago, most of which consists of marine waters and is still lagging behind, it seems that the urgency of tourism in NTT is dominated by sea tourism or nature, such as national parks, Marine Conservation Areas, and Nature Parks (TWA). This is evident through the existence of 8 (eight) marine waters conservation areas owned by NTT Province. In addition, NTT Province also has a lot of potential in the marine sector, such as marine resources for capture and aquaculture; the potential for seaweed cultivation; potential of salt resources; and the potential for pearl cultivation, all of the marine potential is very supportive and influences the urgency of tourism for the East Nusa Tenggara (NTT) Province. Efforts that can be made in order to deal with these challenges include: first, make improvements in the infrastructure sector, for example there is good coordination between the central and regional governments and cities in the NTT Province with regard to policies on water conservation area management or marine tourism in East Nusa Tenggara (NTT); second, maximizing the tourism potential in NTT through professional human resource de-velopment, improved tourism management facilities and third, online tourism publications optimized so that tourists are interested in traveling to the NTT Province; and in addition, supervise/control the applicable laws and regulations in ALKI that cross the sea waters, so that the existence of the ALKI does not interfere with the conservation of waters in the Sawu Sea.